Body-Weight Fluctuation Was Associated With Increased Risk for Cardiovascular Disease, All-Cause and Cardiovascular Mortality: A Systematic Review and Meta-Analysis - Zou, Huajie; Yin, Ping; Liu, Liegang; Liu, Wenhua; Zhang, Zeqing; Yang, Yan; Li, Wenjun; Zong, Qunchuan; Yu, Xuefeng (Frontiers in Endocrinology, 2019)
Background: The aim of this study was to evaluate associations between body-weight fluctuation and risk of mortality and cardiovascular diseases (CVD). Methods: PubMed, EMBASE databases and Cochrane Library were searched for cohort studies published up to May 20, 2019, reporting on associations of body-weight fluctuation and mortality from all causes, CVD and cancer, as well as morbidity of CVD and hypertension. Summary relative risks (RRs) were estimated using a random-effects model. Results: Twenty-five eligible publications from 23 studies with 441,199 participants were included. Body-weight fluctuation was associated with increased risk for all-cause mortality (RR, 1.41; 95% confidence interval (CI): 1.27-1.57), CVD mortality (RR, 1.36; 95% CI 1.22-1.52), and morbidity of CVD (RR, 1.49, 95% CI 1.26-1.76) and hypertension (RR, 1.35, 95% CI 1.14-1.61). However, there was no significant association between weight fluctuation and cancer mortality (RR, 1.01; 95% CI 0.90-1.13). No evidence of publication bias was observed (all P > 0.05) except for studies on all-cause mortality (Egger‘s test, P = 0.001; Begg’s test, P = 0.014). Conclusions: Body-weight fluctuation was associated with higher mortality due to all causes and CVD and a higher morbidity of CVD and hypertension. Key Words: body-weight fluctuation, weight cycling, mortality, CVD, meta-analysis